2011
DOI: 10.1007/s10096-011-1374-z
|View full text |Cite
|
Sign up to set email alerts
|

Be alert to tuberculosis-mediated glomerulonephritis: a retrospective study

Abstract: Mycobacterium tuberculosis infection causing glomerulonephritis is a rare disorder. This retrospective study analyzed the clinical characteristics of patients diagnosed with tuberculosis-mediated glomerulonephritis (TB-GN) between 2002 and 2009, as well as the diagnostic tools used. These findings were then compared with those of patients with primary glomerulonephritis (P-GN). The records of all patients were reviewed. The diagnosis of TB-GN was based on renal hematuria and/or proteinuria and cure after antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…According to a previous study, 43 patients who meet the following criteria can be diagnosed with TB-IgAN: (1) evidence of MTB infection, (2) elevated serum levels of a specific circulating immune complex in TB and reduced serum complement component 3 levels, (3) clinical manifestation of renal involvement, (4) renal pathological changes that are consistent with IgAN and exclude renal TB, (5) exclusion of secondary IgAN, and (6) MTB -specific antigen deposition in renal tissues.…”
Section: Diagnosis and Differential Diagnosis Of Tb-iganmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous study, 43 patients who meet the following criteria can be diagnosed with TB-IgAN: (1) evidence of MTB infection, (2) elevated serum levels of a specific circulating immune complex in TB and reduced serum complement component 3 levels, (3) clinical manifestation of renal involvement, (4) renal pathological changes that are consistent with IgAN and exclude renal TB, (5) exclusion of secondary IgAN, and (6) MTB -specific antigen deposition in renal tissues.…”
Section: Diagnosis and Differential Diagnosis Of Tb-iganmentioning
confidence: 99%
“…MTB DNA detected by polymerase chain reaction in renal biopsy specimens has a considerably increased positive rate compared with that found with urine culture. 43 Therefore, MTB DNA detection in renal biopsy tissues could be used to verify the diagnosis of TB-IgAN. A current study also showed that ESAT-6 could assist in the early diagnosis of IgAN caused by MTB infection.…”
Section: Diagnosis and Differential Diagnosis Of Tb-iganmentioning
confidence: 99%
“… 24 Sun et al found that DNA-extraction steps could cause a substantial loss of mycobacterial DNA. 25 However, our findings still indicate that real-time PCR is an instant and effective diagnostic tool for suspected UTB patients. Although DNA does not replace conventional diagnostic tests completely, it is an indispensable complement.…”
Section: Discussionmentioning
confidence: 68%
“…The classical presentation involving the urinary collecting system is usually diagnosed on microbiological and radiological investigations. Isolated renal parenchyma involvement, including interstitial nephritis and glomerulonephritis, is uncommon, and there is sparse literature on the utility of renal biopsy in these patients 18…”
Section: Discussionmentioning
confidence: 99%